Efficient Day-Ahead Scheduling Voltage Control Scheme of ULTC and Var of Distributed Generation in Distribution System - Kun-Yik Jo (IEEE, 2021)
Most conventional voltage control schemes in distribution systems are controlled through the tap change of the transformer. However, as large-capacity distributed generations (DGs) are connected to the distribution system, this leads to a new voltage problem. In this paper, we propose a day-ahead scheduling voltage control scheme of under load tap changer (ULTC) and reactive power of DGs in distribution system. The proposed control scheme improves both voltage profile and quality, and it determines the reactive power reference value for the real power output of DGs as well as the sending end reference voltage of the distribution substation. To account for prediction error, the reactive power reference values of DGs are determined for a real power output section. This can mitigate the uncertainty problem and the prediction error problem of DGs with intermittent characteristics. The proposed control scheme is also a very practical control scheme because it can be applied to the existing control systems of voltage control devices. The proposed control scheme is formulated as a quadratic programming (QP) problem, and it is compared with the conventional voltage control scheme in test 32-bus and modified IEEE 69-bus radial distribution systems; the control effect and results verify the effectiveness of the proposed control scheme.